The Role of Earthworms as Bioindicators of Heavy Metal Concentrations in Soil Fauna within Mubi North Local Government Area, Adamawa State - Bode A. S; Adamu M. Y; Abdulnasir M (African Journal of Biochemistry and Molecular Biology Research, 2026)
Heavy metal contamination in agricultural soils poses ecological and public health concerns, requiring reliable biological indicators for monitoring soil quality. This study examines the role of earthworms as bioindicators of heavy metal contamination in Mubi North Local Government Area, Adamawa State, Nigeria. Earthworm samples were collected from two farms and analyzed for concentrations of chromium (Cr), copper (Cu), manganese (Mn), nickel (Ni), and zinc (Zn). The results revealed that copper had the highest concentration, followed by nickel and zinc, while manganese and chromium were comparatively lower. Pearson correlation analysis showed that chromium and nickel exhibited moderate positive correlations across both farms, suggesting possible common sources or similar uptake mechanisms. Manganese showed a weak correlation in Farm 1 but a stronger correlation in Farm 2, indicating site-specific environmental influences. In contrast, copper and zinc showed consistently weak correlations, suggesting that their accumulation may be influenced by localized environmental factors. Comparisons with World Health Organization permissible limits indicated that copper and nickel concentrations were relatively high, raising concerns about potential ecological risks and human health impacts through bioaccumulation in the food chain. These findings support the use of earthworms as reliable bioindicators of soil contamination because of their sensitivity to environmental pollutants and capacity to accumulate heavy metals. The study contributes to environmental monitoring and soil quality assessment by demonstrating the relevance of earthworm-based biomonitoring in agricultural ecosystems and highlights the need for regular environmental surveillance and sustainable agricultural practices in Mubi North to protect soil health and public welfare.